A Framework for sizing, designing, and testing of Electrical Power System for nanosatellites: A case study of a 3U university Cubesat - Youssef El Hachimi; Amina Daghouri; Hassane Mahmoudi; Abdelaali Ouhammam; Soumia El Hani (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Because a CubeSat’s Electrical Power System (EPS) must endure the hostile space environment, which includes radiation, temperature fluctuations, and electrostatic discharge, its dependability is essential to the mission’s success. Based on real-world mission experience, this study presents the first organized paradigm that addresses the whole CubeSat EPS development lifecycle, including sizing, design, integration, and qualification. By conforming to the project life cycles of the National Aeronautics and Space Administration (NASA) and the European Cooperation for Space Standardization (ECSS), the framework guarantees adherence to space standards and facilitates the early detection of possible design flaws. In order to guarantee energy sufficiency before hardware development, the framework offers early insights into power generation, storage needs, and subsystem consumption through its Mission Design and Preliminary Power Budget phases. While SIMULINK facilitates preliminary electromagnetic compatibility (EMC) analysis, which aids in identifying design hazards associated with heat dissipation and conducted emissions, COMSOL Multiphysics is utilized for thermal evaluation during the EPS Design phase. By addressing important concerns prior to manufacturing, these early tests increase reliability and lower development costs. The robustness and practical use of the suggested methodology are illustrated by a real-world CubeSat case study, which validates each stage through hardware implementation and environmental and functional testing. In addition to addressing a significant vacuum in the literature, this study enables more dependable and reproducible CubeSat EPS designs for upcoming space missions by offering a comprehensive, mission-driven, and standards-compliant development approach.